Behind the mountains - Danticat, Edwidge, 1969- (New York : Scholastic, 2002)
Writing in the notebook which her teacher gave her, thirteen-year-old Celiane describes life with her mother and brother in Haiti as well as her experiences in Brooklyn after the family finally immigrates there to be reunited with her father.
G8
Keywords: Haitian Americans -- Juvenile fiction; Haitian Americans -- Fiction; Immigrants -- Fiction; Emigration and immigration -- Fiction; Diaries -- Fiction; Haiti -- Fiction; Brooklyn (New York, N.Y.) -- Fiction